TINJAUAN PROSES KREATIF MAHASISWA DESAIN PRODUK PADA PROSES DESAIN TUGAS AKHIR (STUDI KASUS: TUGAS AKHIR DESAIN PROUK MAINAN) - Hady Soedarwanto (Universitas Mercu Buana, 2020)
To complete a design requires a series of processes that must be presented in the designer's mind. There are many design methods that are learned in learning to design to produce extraordinary designs and can solve problems as a philosophical basis for design activities. In the toy product design process has a fundamental goal, which is to achieve fun (fun) to its users, through the fulfillment of aspects of function, fulfillment of aspects of the system and fulfillment of aesthetic aspects. The Final Assignment course was chosen to be sampled because this course was followed by the final year students who had experienced several design methods, so that by reviewing their process of completing the final assignment course it was hoped that a more significant creative process would be found in solving problems especially in the field of product design toy. Data obtained by taking the Final Project with the title of toy product design. Data collection is also carried out by in-depth interview methods in the process of assistance and design testing and then analyzed using the theory of design methods (design methods) and the theory of creative processes (creative thinking). The results of this study are expected to be a tendency of students (designers) to complete their design projects. know the aspects of concern and to find out their strategies in overcoming design problems.